(untitled) (Journal of Hama University, 2026)
Printing is currently one of the most prominent processes used for fabric decoration. It is a popular process used as a step in the textile manufacturing process to enhance the aesthetic appearance of fabrics and satisfy the buyer’s taste. Printing pastes contain several components, including thickeners, which are responsible for imparting viscosity to the pastes, controlling the paste’s penetration into the fabric and achieving fine edges for the printed designs. Natural thickeners are important as readily available materials and a more suitable alternative to synthetic thickeners. This research focuses on studying the viscosity behavior of pastes containing some natural thickeners, such as guar gum, starch, and sodium alginate, depending on the applied shear stresses. During the printing process, the paste is exposed to shear stresses applied by the scraper, leading to a decrease in its viscosity. The behavior of binary mixtures of thickeners was also studied. It was found that a paste containing a 50/50 mixture of guar gum and sodium alginate exhibited behavior and viscosity values suitable for printing.